Formation of the Life Competence of 6–7 Year-Old Children in the Gaming Activity - Olena Sas (Pedagogical Discourse, 2013)
In the article the actual problem of the formation of life competence of 6–7 year-old children is revealed, the research approaches of teachers and psychologists to the solving of the question of formation of life competence of children this age are analyzed. The study focuses on the need to incorporate the essence of the child's personality role in the formation of life competence. It submits a detailed description of the game and reveals its importance in shaping of the life competence of 6–7 year-old children. It is established that the child acquires in the game experience, which is important for the formation of life competence.